Implementation of a Thermoelectric Generator Series Circuit to Increase the Output Voltage by 5V as a HT charger to support TNI duties - Kasiyanto Kasiyanto; Wahyu Imam Fauzi Wibisono; Aguk Sridaryono; Yuri Arianto (Pustaka Poltekad, 2025)
This research aims to implement a TEG series circuit to achieve an output voltage that exceeds 5V, so that it can charge the HT. The method used in this research involves configuring several TEG modules in series to increase the overall voltage. This research begins with selecting an appropriate TEG and arranging it into a series circuit, followed by testing to measure the output voltage and system efficiency at variable temperatures. Trials also prove that increasing the module in a series circuit can significantly increase the output voltage, but temperature and electrical stability require special attention to improve equipment performance. The conclusion of this research is that the TEG series circuit is more effective in increasing the output voltage for HT charging. with results according to the desired target. Suggestions for further research include exploring the use of the TEG module to get maximum results, as well as developing a better temperature management system to optimize performance in real conditions. This research provides a clear basis for the development of TEG-based charging technology in other applications that require high voltage.